2016
DOI: 10.1094/cchem-05-16-0153-r
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Microbial Load of Wheat by Tempering with Organic Acid and Saline Solutions

Abstract: Reducing microbial contamination in wheat is desirable to ensure consumer safety. In this study, the efficacy of adding organic acids and NaCl to tempering water to reduce microbial contamination in hard wheat was evaluated. Hard red winter wheat was tempered to 15.5% moisture by adding sterile distilled water (control) or tempering solutions containing organic acids (acetic, citric, lactic, or propionic; 1.0, 2.5, or 5.0 v/v), NaCl (26 or 52% w/v), or a combination of organic acid (acetic or lactic; 2.5 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
6
27
0
Order By: Relevance
“…NaCl and organic acids differ in their mechanisms of microbial inhibition. Similar reduction levels in APC counts were observed in a previous study after tempering hard wheat with organic acid solutions (Sabillón, Stratton, Rose, Flores, et al, 2016). Tempering solutions containing a 2.5% acetic acid concentration caused a reduction of 0.90 ± 0.21 log CFU/g in the aerobic bacteria population.…”
Section: Inactivation Of Wheat Natural Microbiota By Tempering Withsupporting
confidence: 88%
See 4 more Smart Citations
“…NaCl and organic acids differ in their mechanisms of microbial inhibition. Similar reduction levels in APC counts were observed in a previous study after tempering hard wheat with organic acid solutions (Sabillón, Stratton, Rose, Flores, et al, 2016). Tempering solutions containing a 2.5% acetic acid concentration caused a reduction of 0.90 ± 0.21 log CFU/g in the aerobic bacteria population.…”
Section: Inactivation Of Wheat Natural Microbiota By Tempering Withsupporting
confidence: 88%
“…Adding NaCl to the tempering solution containing 5.0% lactic acid further increased the microbial reduction from 1.92 ± 0.11 to 3.07 ± 0.10 log CFU/g for APC and from 3.13 ± 0.32 to 4.49 ± 0.0 log CFU/g for Eb, which suggests a synergistic interaction (Figures 1 and 2). In a previous study, a strong synergistic interaction between lactic acid and NaCl was observed against the natural microbiota of hard wheat (Sabillón, Stratton, Rose, Flores, et al, 2016), which was attributed to the ability of lactic acid to permeate and disrupt the microbial cell membrane, thus facilitating the diffusion of NaCl ions into the cytoplasm. Moreover, this tempering solution reduced the Eb (4.49 ± 0.0 log CFU/g), coliform (3.52 ± 0.0 log CFU/g), yeast (2.69 ± 0.0 log CFU/g), and mold (3.47 ± 0.0 log CFU/g) populations to levels that were below the limit of detection of the methods used to quantify F I G U R E 2 Effect of tempering with water or solutions containing a combination of salt and organic acid on reducing the microbial load of soft wheat.…”
Section: Inactivation Of Wheat Natural Microbiota By Tempering Withmentioning
confidence: 92%
See 3 more Smart Citations